About Methods of Language Teaching - Mamadayupova Vasila Shonazarovna; Oso Micheal Olamide (Researchparks Publishing, 2022)
At present stage of development of science, technology, international trade, different types of business communication a good command of foreign languages is not only a necessity, but also the need for specialists. There are many traditional methods of teaching foreign languages which are quite effective. However, the current development of society requires finding and using more advanced techniques and technologies.